The influence of experience and expertise on how surgeons prepare to perform a procedure. Issue 10 (28th June 2021) - Crebbin, Wendy; Guest, Glenn; Beasley, Spencer; Tobin, Stephen; Duvivier, Robbert; Watters, David
Abstract: Background: There is a paucity of literature describing how surgeons (either novice or expert) mentally prepare to carry out a surgical procedure. This paper focuses on these processes, and is part of a larger piece of research based on the Royal Australasian College of Surgeons (RACS) Clinical Decision Making model. Methods: Interviews were conducted over a 3‐year period with registrars, trainees, fellows and consultants in the Department of Surgery at one large regional hospital in Victoria. Analysis began from the first interview with no pre‐conceived codes. Emerging themes were drawn from participants' interpretation of their experiences. Further information was obtained during discussions in theatre while patients were being prepared for surgery. Results: The findings show that the process of rehearsal changes as a surgeon gains more experience in a procedure. A 'novice' relies on external sources of information, for example textbooks and videos. After participating in a number of similar procedures their reliance gradually moves to their own sensory memories. Surgeons at all levels of experience discuss their preparations with peers, colleagues, senior clinicians, and where appropriate, with members of other disciplines. Conclusion: These findings offer insight into how surgeons, at different levels of experience, prepare for a procedure. These understandings have the potential to improve the teaching and learning of this essential component of surgical practice. Abstract : There is a paucity of literature describing how surgeons (either novice or expert) mentally prepare to carry out a surgical procedure. This paper, focusing on these processes, demonstrates some of the transitions from novice to expert surgeons. These findings offer a potential to improve teaching and learning this essential component of surgical practice.